Trends of Rainfall in Sri Lanka over the Last Century - Jayawardene, H.K.W.I.; Sonnadara, D.U.J.; Jayewardene, D.R. (My University, 2005)
Utilizing over 100 years of rainfall records in 15 meteorology stations, an analysis was carried out to extract the trends of annual rainfall depth in Sri Lanka over the last century. A statistically significant increasing trend of rate 3.15 mm/year was observed at Colombo and decreasing trends were observed at Nuwara Eliya and Kandy with rates of 4.87 mm/year and 2.88 mm/year respectively. Since no coherent increase or decrease of rainfall in any group of stations in the wet or dry zones was observed, the possibility of large scale change over the past century was ruled out. However, more recent data records (1949 onwards), revealed a decreasing trends in 13 of the 15 stations. Thus, traces of a temporal change seem to be apparent in the rainfall records over the last half century. In general, the downward trends in recent decades are steeper than the long term variations. For the recent data records, the largest downward trend of 11.16 mm/year was observed at Batticaloa.
Keywords: Rainfall; Last Century; Trends